P17.11 Public sexual health clinics increase access, hiv testing and re-testing among higher risk gay and bisexual men. (13th September 2015) - Jamil, MS; Callander, D; Ali, H; Prestage, G; Knight, V; Duck, T; O'Connor, CC; Chen, M; Hellard, M; Grulich, A; Wilson, D; Kaldor, J; et al.
Abstract : Introduction: Most HIV diagnoses in Australia occur in gay and bisexual men (GBM), however the majority of higher-risk GBM are testing for HIV at less than recommended frequency (3–6 monthly). In recent years, public sexual health clinics (SHCs) have implemented a range of initiatives to increase access to HIV testing in GBM including express clinical models, after-hours/drop-in services, online-booking, rapid-testing, and SMS reminders. We measured HIV testing trends among GBM at New South Wales (NSW) SHCs in the time period of the initiatives. Methods: We utilised routinely collected data from 33 SHCs in NSW, and calculated the following annual indicators among HIV negative GBM from 2009–2013: number attending clinics; proportion tested for HIV at least once; proportion re-tested within 1–12 months; and HIV positivity. Indicators were calculated for all GBM and higher-risk GBM (>5 partners in last 3 months or previous sexually transmissible infection diagnosis). Chi-square tests were used to assess trends over time. Results: In the 5-year period, 29, 623 unique HIV-negative GBM attended participating SHCs and 21% were higher-risk men. Among all HIV-negative GBM, there were significant increasing trends (p-values <0.001) in: the number of individuals attending (4, 748 in 2009 to 7, 387 in 2013, relative increase:56%); proportion tested (73% to 85%, relative increase:16%); and proportion re-tested within 1–12 months (42% to 52%, relative increase:24%). Among higher-risk GBM, greater increases were observed in individuals attending (934 to 1, 667, relative increase:78%) and proportion re-testing (51% to 64%, relative increase:26%), but a smaller change in the proportion tested (89% to 93%, relative increase:5%), though starting from a higher base (significant increasing trends, p-values <0.001). HIV-positivity in all GBM fluctuated (1.3–1.1%) with no significant trend over time (p = 0.790). Conclusion: NSW SHCs have successfully increased attendance and HIV testing among GBM, particularly in higher-risk men. HIV-positivity suggests that testing increases have been well-targeted to higher-risk GBM. There is potential to further improve testing uptake and re-testing. Disclosure of interest statement: ACCESS study is funded by the NSW Ministry of Health and the Victorian Department of Health.